CONTRIBUTION TO THE IMPROVMENT OF CONDENSED MILK PRODUCED IN GREECE - ΣΚΟΥΝΤΖΟΣ, Κ.; ΠΑΠΑΔΙΑ, Α.; ΓΙΩΤΗΣ, Α. (Journal of the Hellenic Veterinary Medical Society, 1972)
In this study the canned, unsweetened, condensed milk produced in Greece was examined. The causes of alteration of this product were investigated in the Laboratory. These causes were : the mediocre quality of the milk used, the lack of pre—cooling rooms, the utilization of common vehicles for transport, the imperfect homogenization, the storage of condensed milk untili the canning at 55° C, the impropre arrangement of cans in the autoclave, the sterilization at low temperature for a short time and the quality of the water used to cool the cans. By applying several sanitary and other measures a product of satisfactory quality has been obtained and this was to the profit of producers as well as of the National Economy.